2000
DOI: 10.1103/physrevlett.85.3628
|View full text |Cite
|
Sign up to set email alerts
|

Strain versus Stress in a Model Granular Material: A Devil's Staircase

Abstract: The series of equilibrium states reached by disordered packings of rigid, frictionless discs in two dimensions, under gradually varying stress, are studied by numerical simulations. Statistical properties of trajectories in configuration space are found to be independent of specific assumptions ruling granular dynamics, and determined by geometry only. A monotonic increase in some macroscopic loading parameter causes a discrete sequence of rearrangements. For a biaxial compression, we show that, due to the sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
130
1
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(151 citation statements)
references
References 13 publications
14
130
1
6
Order By: Relevance
“…Here we deal with rigid (undeformable) grains with help of the simulation technique of contact dynamics [10,11] therefore elastic deformations are excluded. As opposed to the weak perturbations, in our case, plastic deformation of the packing is initiated [3,4]. Plastic rearrangements caused by local perturbations have been studied in recent experiments [5] where interesting power law decay of the rearrangement field was found.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Here we deal with rigid (undeformable) grains with help of the simulation technique of contact dynamics [10,11] therefore elastic deformations are excluded. As opposed to the weak perturbations, in our case, plastic deformation of the packing is initiated [3,4]. Plastic rearrangements caused by local perturbations have been studied in recent experiments [5] where interesting power law decay of the rearrangement field was found.…”
mentioning
confidence: 99%
“…When the external load on a static assembly of grains is changed at a certain point the load may become incompatible with the inner structure of the packing and the solid state looses its stability. How exactly this happens on grain-scale and what are the key features of the transition between statics and flow are intriguing and unresolved problems [3,4,5,6]. Moreover, it is of essential importance in many applications to be able to predict, initiate or prevent such transitions.…”
mentioning
confidence: 99%
“…Consequently, for infinitesimal deformations around a reference state, a granular packing should possess a true elastic response and displays no ageing [31]. Note however, in the limit of very small if not zero friction the establishment of a linear elastic response under finite shear is questionable [32]. Moreover, for real granular materials, the actual pressures at contact are generically high and contacts may creep plastically.…”
mentioning
confidence: 99%
“…Despite these successes, the hypothesis of linear marginal stability yields an incomplete insight on the non-linear processes occurring in amorphous materials, which are critical to understand plasticity, thermal activation or granular flows [7]. When interactions are short-range one key source of non-linearity is the creation or destruction of contacts between particles [8,9]. Combe and Roux have observed numerically [8] that such rearrangements occur intermittently, in bursts or avalanches whose size is power-law distributed, a kind of dynamics referred to as crackling noise [10].…”
mentioning
confidence: 99%
“…When interactions are short-range one key source of non-linearity is the creation or destruction of contacts between particles [8,9]. Combe and Roux have observed numerically [8] that such rearrangements occur intermittently, in bursts or avalanches whose size is power-law distributed, a kind of dynamics referred to as crackling noise [10].Interestingly some glassy systems with long-range interactions display such dynamics, in particular Coulomb glasses [11] and mean-field spin glasses [12]. In both cases the requirement of stability toward discrete excitations (flipping two spins or moving one electron) leads to bounds on important physical quantities: Efros and Shklovskii showed that the density of states in a Coulomb glass must vanish at the Fermi energy [13], implying the presence of the so-called Coulomb gap.…”
mentioning
confidence: 99%